Water expenditure, service quality and inequality in Latin America and the Caribbean - María Pérez-Urdiales; Carolina Tojal Ramos dos Santos (Inter-American Development Bank (IDB), 2024)
Latin America and the Caribbean (LAC) countries have made notable progress in reducing income inequality; however, the extent to which water and sanitation may foster inequalities remains unclear. In this sector, disparities emerge as lower-income households may encounter reduced access to clean water, utilize less water, or bear a disproportionately higher financial burden than higher-income households. In this paper, we investigate latter source of inequality in the water and sanitation sector in LAC. We analyze and compare inequality measures for water expenditures and income for Brazil, Colombia, Costa Rica, and Uruguay using survey data from the Americas Barometer of the Latin American Opinion Project (LAPOP). Our descriptive analysis indicates that low-income households allocate a larger proportion of their income to water expenditures compared to high-income households. By comparing the water concentration curve to the Lorenz curve for each country, we find that water expenditures are generally more equitably distributed than income, leading to an unequalizing effect, as households spend similar amounts regardless of income level. Additionally, we demonstrate that total water expenditures, encompassing tap water, bottled water, and water delivered by trucks, align more closely with income distribution than tap water alone in Brazil, Costa Rica, and Uruguay, whereas the opposite is true for Colombia. These disparities may be attributed to water tariff subsidies and the higher consumption of bottled water among wealthier households.
Keywords: Q21; O13; O54; Q25; 330; water expenditures; water quality issues; inequalities; water inequalities; Latin America and the Caribbean